Description of the Cities and the Lives of the Peoples in Transoxiana, Kabul, Ghazni, and India in the Tenth Century AH / Sixteenth Century AD (The "Babur Nama" as a Source): A Study in Historical Geography - Al Jawarneh, Ahmed M. (Jordan Journal for History and Archaeology, 2026)
The memoirs of the Mongol king Babur are among the most prominent historical and cultural sources for the peoples of Central Asia and the Indian subcontinent in the fifteenth and sixteenth centuries AD. The memoirs are in three parts, the first in Ferghana (Uzbekistan), covering 899 AH/1493 AD - 909 AH/1503 AD, the second in Kabul (Afghanistan), covering 910 AH/1504 AD - 931 AH/1524 AD, and the third in Delhi (India and Pakistan) covering 932 AH/1525 AD - 936 AH/1529 AD. Babur began writing his memoirs after 934 AH/1527 AD, that is, one year after his occupation of India and his establishment of the Mughal (Timurid) state on the throne of Delhi and thirty years since the start of his rule in Ferghana in 900 AH/1494 AD. What concerns us in this study is shedding light on Babur’s description of cities and the lives of peoples in Central Asia, Afghanistan, Pakistan, and India in the sixteenth century. This study seeks to address many issues, foremost among them: the nature of the cities that spread in Transoxiana, Afghanistan, and India, how those cities were cared for by the Islamic families who established their rule prior to the study period, and the importance of Babur’s memoirs.